PENGARUH KOMPETENSI, MOTIVASI DAN JIWA INTRAPRENEURSHIP TERHADAP KINERJA KARYAWAN (Penelitian Pada Karyawan Senior Staff PT. Indo-Rama Synthetics Tbk Divisi Polyester) - Yana Ernawan; Nanang Wahidin (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
This study aims to examine the influence of competence, motivation, and mental of intrapreneurship on the employee performance of senor staff of PT. Indo-Rama Synthetics Tbk Polyester Division at a Jatiluhur Purwakarta. Based on the theoretical model proposed in this study used a statistical technique is multiple linear regression. The population is 238 people, using a probability sampling methods, approaches Area (Cluster) Sampling, then taken as many as 70 samples. The results showed that all the variables (competence, motivation, and mental of intrapreneurship) are a positive influence on employee performance. The results of this study can be a reference for the various parties to improve employee performance. Hence, need more attention of the employees, especially in improving the competence, motivation and mental of intrapreneurship through training and development continuously. Keywords : competence , motivation , mental of intrapreneurship , and employee performance